2022
DOI: 10.1620/tjem.2022.j002
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Urinary Exosomal miRNA in Idiopathic Membranous Nephropathy and Evaluation of its Diagnostic Value

Abstract: Urinary exosomal miRNA is an ideal non-invasive biomarker of renal disease, but little is known about its ability to diagnose idiopathic membranous nephropathy (IMN). The purpose of this study was to explore the clinical value of urinary exosomal miRNAs in IMN. Urine samples were collected from 36 IMN patients and 36 healthy subjects. Some samples were used to analyze the miRNA profiles of urinary exosomes by high-throughput sequencing. The remaining cases were verified by reverse transcription-quantitative po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The target genes of these miRNAs are widely involved in pathway responses such as podocyte autophagy and macrophage inflammation. 2022, in Datong, Shanxi, Songjia Guo et al (2022) run high-throughput miRNAs sequencing of urinary exosomes. Results showed that miR-30b-5p and miR-9-5p were significantly downregulated in PMN patients compared with healthy people.…”
Section: Microrna: Biological Function and Action Formationmentioning
confidence: 99%
“…The target genes of these miRNAs are widely involved in pathway responses such as podocyte autophagy and macrophage inflammation. 2022, in Datong, Shanxi, Songjia Guo et al (2022) run high-throughput miRNAs sequencing of urinary exosomes. Results showed that miR-30b-5p and miR-9-5p were significantly downregulated in PMN patients compared with healthy people.…”
Section: Microrna: Biological Function and Action Formationmentioning
confidence: 99%
“…Thus, we speculate that sEV-ncRNAs contribute to the initiation and development of kidney diseases, although the precise mechanism remains to be determined. Secondly, sEV-ncRNAs have shown an exceptional value for diagnosing kidney diseases ( Li et al, 2022 ; Guo et al, 2022 ). At present, the global research efforts primarily focus on exploring the possibility of using sEV-ncRNAs as diagnostic tools for kidney diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, only a few scholars are exploring the diagnostic value of sEV-miRNAs in IMN. Guo et al (2022) investigated the expression profile of urinary sEV-miRNA in IMN patients and found that miR-30b-5p and miR-9-5p were markedly downregulated in patients with IMN as compared to healthy controls. In their study, the potential diagnostic value for IMN of miR-30b-5p and miR-9-5p was also demonstrated by the authors through ROC curve analysis.…”
Section: Roles Of Sev-ncrnas In Imnmentioning
confidence: 99%
“…In this regard Lange and colleagues have shown that miRNA 21 levels are increased in uEVs in individuals with diabetes as well as a mouse model of glomerulonephritis [74]. Similarly, unique miRNA profiles in uEVs have been reported in individuals with membranous nephropathy [75], hypertension with albuminuria [76], diabetic kidney disease [77], [78], SLE [79], and Fabry nephropathy [80]. Recently, Luan et al reported changes in the profile of circular RNAs in uEVs from individuals with IgA nephropathy as compared to healthy subjects [81].…”
Section: Evs In Glomerular Diseasementioning
confidence: 94%